Vanalakshmi, an Agro-Forestry Project in Kerala - Nair, P. N. (Indian Forester, 1980)
Till recently the forest areas including forest plantations were intented only for production of timher and other forest produces. In Kerala where population is heavy, land scare, forests limited in extent and agro-c1imatic conditions highly suitable for many cash crops, agro-forestry and multiple cropping are desirable and possible in selected plantation areas. Recently the Kerala forest department has launched a novel scheme of cultivating cash crops such as pepper and cocoa and also valuable medicinal plants as an inter (under) crop in selected areas within forest plantations of Teak, Bombax, Silver oak, Aini etc. The scheme locally known as Venalakshmi scheme was commenced in 1979-80 and will cover 1800-2000 ha in five years. In teak plantations on the banks of perennial streams and rivers, in which final thinning operations have been completed pepper is grown on teak as well as newly introduced additional standards, and cocoa and medicinal plants planted in the interspace, with all facilities for intensive management. Similarly pepper is grown in other plantations such as Aini, Bombax and Silver oak in their early stages. The scheme is financially viable. From the observations made so far the results are highly encouraging and it is hoped that more and more plantation areas can be brought under this scheme. The main advantages are: (I) no forest area is lost, (2) production of crops such as pepper, cocoa and medicinal plants, is possible without affecting timber production in the same area, (3) generates rural employment particularly to the tribals, (4) increases revenue returns from the same area, (5) does not deteriorate the environment otherwise contributed by forest plantations.